Men's Objectification of Women in the Novel "Naqah Shalihah" by Saud Al Sanousi - Indah Lutfiyati; Rizqi Handayani (Litteratura: Jurnal Bahasa dan Sastra, 2023)
Since the 20th century up to the present day, the objectification of women is still a central phenomenon in feminist discourse, particularly in the Arab cultural context such as in Kuwait. One tradition that serves as a fertile ground for this issue is the practice of forced arranged marriages, as discussed in the novel "Naqah Shalihah" by Saud al-Sanousi. This novel presents issues related to the culture of forced marriages towards women in the Badui tribe, which gives rise to men's objectification of women. This research aims to analyze the various forms of male objectification of women present in the novel "Naqah Shalihah" by Saud al-Sanousi. The research method used is descriptive analytics with a feminist literary criticism approach and the theories of objectification by Martha Nussbaum and Rae Langton. In the process, data is collected and then analyzed using content analysis techniques. The results of the data analysis indicate nine forms of male objectification of women, namely instrumentality, denial of autonomy, ownership, denial of subjectivity, inertness, violability, fungibility, reduction to body, and reduction to appearance.